Correcting the past failures to replicate Psi. [article]. - Galak, Jeff.
Across 7 experiments (N=3,289), we replicate the process of experiments 8 and 9 from Bem (2011), which had originally demonstrated retroactive facilitation of recall. We failed to replicate that finding average effect size is (d=0.04) is no different from O. We discuss some reasons for differences between the results in this article and those presented in Bem (2011). - (from the authors)
Keywords: LeBoeuf, Robyn A; Psi; Recognition; ESP; Researcher degrees of freedom; Meta-analysis.